A conceptual framework to assess development of smallholder crop-cattle farming systems in Bhutan: Sustainable development or Gross National Happiness? - Samdupa, T.; Udo, H.M.J.; Eilers, C.H.A.M.; Ibrahim, Mohamed N.M.; Zijpp, A.J. van der (2010)
The objective of this paper is to compare the concepts of Sustainable Development (SD) and Gross National Happiness (GNH) to assess development at various level, especially at the smallholder crop-cattle farming systems level in Bhutan. The concept of SD was conceived about two decades ago, while GNH is a development paradigm that drew international attention in 1998. In this paper the similarities and differences of the SD and GNH concepts and their application to the case in Bhutan are reviewed. The generally cited four pillars of GNH are proposed as "building blocks" of GNH. They are sustainable and equitable socio-economic development, ecological preservation, preservation and promotion of culture and good governance. A conceptual framework to assess context dependent issues of GNH is developed. It is concluded that GNH assessment may be more appropriate at higher systems levels (e.g. district, national level) since it is at these level that the "building blocks" of GNH constitutes a useful framework through which regional and national development can be actualized. At present, for farm level assessment SD could be more appropriate since the indicators for the "building blocks" of GNH such as culture and good governance are still very few, qualitative and rather vague.